Polymorphysims of CYP17-I Gene in the Exons Were Associated with the Reproductive Endocrine of Japanese Flounder (Paralichthys olivaceus) - Ma, R Q (Asian-Australasian journal of animal sciences, 2012)
The cytochrome P450c17-I (CYP17-I) is one of the enzymes critical to gonadal development and the synthesis of androgens. Two single nucleotide polymorphisms (SNPs) were detected within the coding region of the CYP17-I gene in a population of 75 male Japanese flounder (Paralichthys olivaceus). They were SNP1 (c.C445T) located in exon2 and SNP2 (c.T980C (p.Phe307Leu)) located in exon5. Four physiological indices, which were serum testosterone (T), serum 17β-estradiol (E2), Hepatosomatic index (HSI), and Gonadosomatic index (GSI), were studied to examine the effect of the two SNPs on the reproductive endocrines of Japanese flounder. Multiple comparisons revealed that CT genotype of SNP1 had a much lower T level than CC genotype (p<0.05) and the GSI of individuals with CC genotype of SNP2 was higher than those with TT genotype (p<0.05). Four diplotypes were constructed based on the two SNPs and the diplotype D3 had a significantly lower T level and GSI. In conclusion, the two SNPs were significantly associated with reproductive traits of Japanese flounder